Characteristics and Predictive Factors for Multidrug-Resistant Gram-Negative Infection Following Deployment-Related Trauma. (4th October 2017) - Campbell, Wesley; Li, Ping; Carson, Leigh; Whitman, Timothy J; Blyth, Dana M; Petfield, Joseph L; Mende, Katrin; Tribble, David R
Abstract: Background: Multidrug-resistant Gram-negative bacilli infections (MDRGNI) in complex polytrauma patients is not well-described despite growing concern for antimicrobial resistance outpacing antimicrobial development. Characteristics and predictors for primary MDRGNI among wounded military personnel (2009-2014) are presented. Methods: Data on infectious outcomes and microbial recovery from US military personnel with deployment-related trauma medevac'd to Germany and transferred to a participating US hospital were collected through the Trauma Infectious Disease Outcomes Study. Multidrug resistance was defined as resistance to ≥3 of 4 antibiotic classes or production of extended spectrum β-lactamase or carbapenemases. Infections were restricted to first diagnosed infection. Logistic regression analysis assessed factors associated with MDRGNI. Results: Among 2699 trauma admissions, 913 (34%) had an infection with 476 (18% of 2699) having a primary GN infection, of which 172 (36%) was MDR and 304 (64%) were susceptible. Among the MDRGNI patients, primary etiologic agents were Escherichia coli (56%), Acinetobacter spp. (47%), and Pseudomonas aeruginosa (16%). Median time to MDRGNI event was 7 days post-trauma with 75% of MDRGNIs diagnosed by 11 days post-trauma. MDRGNI patients had longer hospitalization (52 vs. 44 days for GN events; P < 0.001). Multivariate analysis identified prior MDRGN colonization (OR: 6.5, 95% CI: 3.8-11.1) as the strongest predictor for MDRGNI. Use of antibiotics ≥2 days identified increasing risk with combinations of First-generation cephalosporin and fluoroquinolone (FQ) (OR: 2.0, 95% CI: 1.2-3.3) and vancomycin and carbapenem (OR: 2.2, 95% CI: 1.2-4). With ≥5 days exposure, risk was significantly increased with Firstgeneration cephalosporin and FQ (OR: 4.9, 95% CI: 1.9-12.5), but not vancomycin and carbapenem. Conclusion: A high proportion of patients in our study had a MDRGNI as their first infection. Increased risk was associated with prior MDRGN colonization as well as escalating antibiotic class, expanded coverage combination regimens, and duration of exposure. As the largest cohort analysis of trauma patients, these findings inform antimicrobial stewardship and infection control practices. Disclosures: All authors: No reported disclosures.